Chromium adsorption using a composite adsorbent of corn waste and bentonite - Miguel Herrera-Gavidia; Dalia Carbonel; Hugo Chirinos-Collantes (Revista Facultad de Ingeniería Universidad de Antioquia)
Chromium, a highly toxic heavy metal, poses significant risks to both human health and environmental quality. Its adsorption in wastewater using low-cost, easily implementable technologies has emerged as a crucial solution for mitigating its harmful impact. This study explores the effectiveness of a composite adsorbent made from bentonite and corn waste for chromium adsorption. Experiments were conducted in a laboratory-scale batch system. The research examined the adsorption kinetics and equilibrium, process optimization, and the mechanisms of chromium adsorption. For optimization, a response surface methodology was applied considering three variables: adsorption time (min), adsorbent dosage (g/L), and initial chromium concentration (mg/L). The findings suggest that the adsorption kinetics fit best with the pseudo-first-order model (R2 = 0.968), and the adsorption equilibrium fits with the Freundlich model (R2 = 0.997). During optimization, the adsorbent dosage emerged as the most critical factor for chromium removal. The optimal operating conditions were determined to be 103 minutes, 29.71 g/L of adsorbent, and an initial chromium concentration of 31.13 mg/L. The results indicate that chromium adsorption is a multifaceted process involving diffusion and subsequent interaction at the surface and edges of the bentonite layers. Chemical analysis, coupled with changes in the FTIR spectrum, suggests an interaction between chromium and the silicon and aluminum components of the bentonite. These findings underscore the potential of the composite adsorbent for effective chromium removal.